ch32-p032 - 32. We use Eq. 32-27 to obtain U = (s,zB) =...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
32. We use Eq. 32-27 to obtain U = – ( µ s,z B ) = – B s,z , where sz e B eh m , 4 π (see Eqs. 32-24 and 32-25). Thus, UB B BB B =−
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

This note was uploaded on 06/03/2011 for the course PHY 2049 taught by Professor Any during the Spring '08 term at University of Florida.

Ask a homework question - tutors are online